Composition and seasonal variation of crab larvae in the Matang Mangrove Forest, Perak - Ibrahim, Norizan (2016)
A study was conducted to investigate the composition and seasonal variation of crab larvae in the Matang Mangrove Forest, Perak from June 2015 to January 2016. The sampling areas were divided into station 1 (MO), considered as least disturbed mangrove, station 2 (MT), was considered as moderately disturbed mangrove and station 3 (MS), was considered as most disturbed mangrove. In total, 9,952 individuals were observed under the microscope for identification. The analysis of water parameter data showed that there were significant (p < 0.05) variations in salinity among the stations and between the seasons. Total catch comprised of 3 major families namely: Leucosiidae (3.19%), Sesarmidae (24.48%) and Porcellanidae (1.40%), with the rest as unidentified (71%). Sesarmidae larvae were the most abundant family, which appeared in every month with the maximum density in December. It was observed that the highest mean density (303.12±150.26 individual/100m3) of crab larvae was at moderately disturbed mangrove (MT) and the lowest mean density (73.22±33.46 individual /100m3) was found in least disturbed mangrove (MO). It is also revealed that highest crab larval density was found in wet season (405.72±154.12 individual /100m3) compared to larval density in dry season (11.18±10.86 individual /100m3). There was a significant (p<0.05) difference between the dry and wet seasons on the basis of all diversity indices of crab larvae.